Coaching insights: Holism in sports coaching: Beyond humanistic psychology - Cassidy, T. (International Journal of Sports Science and Coaching, 2011)
Increasingly the professional development literature in sports coaching encourages coaches to coach holistically. Yet the phrase `holistic coaching` is mired in ambiguity and has the potential to become meaningless. The aims of this article are to explore the relationship between holism, humanistic psychology, humanism and sports coaching, and to pose some challenges, which could support the field to move beyond the influence of humanistic psychology. Commentary S. 445-501